Performance of digital filtering and synchronization method for APD communication receiver - Hui-Jun Zhang; Peng Lin; Tong Wang; Zi-Qi Zhang; Bai-Qiu Zhao; Wen-Fang Jiao; Xiao-Nan Yu (Journal of Electronic Science and Technology)
Optical wireless (OW) communication systems face significant challenges, such as signal attenuation due to atmospheric absorption, scattering, and noise from hardware components, which degrade detection sensitivity. To address these challenges, we propose a digital processing algorithm that combines finite-impulse response filtering with dynamic synchronization based on pulse addition and subtraction. Unlike conventional methods, which typically rely solely on hardware optimization or basic thresholding techniques, the proposed approach integrates filtering and synchronization to improve weak-signal detection and reduce noise-induced errors. The proposed algorithm was implemented and verified using a field-programmable gate array. Experiments conducted in an indoor OW communication environment demonstrate that the proposed algorithm significantly improves the detection sensitivity by approximately 6 ​dB and 5 ​dB at communication rates of 3.5 Mbps and 5.0 Mbps, respectively. Specifically, under darkroom conditions and a bit error rate of 1 ​× ​10−7, the detection sensitivity was improved from −38.56 dBm to −44.77 dBm at 3.5 Mbps and from −37.12 dBm to −42.29 dBm at 5 Mbps. The proposed algorithm is crucial for the future capture and tracking of signals at large dispersion angles and in underwater and long-distance communication scenarios.